Description of electric field-dependent dielectric permittivity in PMN ceramics - Lima, E. C.; Guerra, J. D.S.; Araujo, E. B. [UNESP] (Taylor & Francis, 2019)
The temperature dependences of the linear and nonlinear components of the dielectric permittivity of PMN ceramics were determined as a function of bias electric fields. The influence of the applied bias electrical field, superimposed to the small signal oscillating electrical field, is investigated. A decrease in the real dielectric permittivity with increasing the applied bias electrical field was obtained for the investigated temperature range. The temperature dependence of the nonlinear dielectric response reveals an anomalous behavior, indicating a phase transition induced by the bias electric field. The present investigation revealed the influence of the bias electric field on the freezing temperature and activation energy. The results were discussed according to a spherical random bond–random field glassy model for relaxors.
Keywords: DC bias electric field; nonlinear dielectric response; PMN